2017
DOI: 10.1039/c7cp03259e
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional NiO nanosheets with enhanced room temperature NO2sensing performance via Al doping

Abstract: High-performance gas sensors based on metal oxides operated at room temperature are of great interest due to their energy saving and cost effective characteristics. How to improve the sensitivity of metal oxide gas sensors and enable their room-temperature operation are challenging for their realistic applications. In this work, we have designed and fabricated Al-doped NiO nanosheets for greatly enhanced NO detection at room temperature. Different amounts of Al were doped into two-dimensional (2D) NiO nanoshee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 56 publications
0
43
0
Order By: Relevance
“…112 The aim of this topical review is to critically evaluate the design and structure of SMON-based gas sensors that may help guide the design of new devices. The performance of these SMON based gas sensors operated at RT could be improved significantly by modifying the SMONs using noble metal nanoparticles, [113][114][115][116] metal ions, [117][118][119] composites of multiple SMONs [120][121][122][123] and carbon nanomaterials. [124][125][126] In addition, not only the quantity of chemisorbed oxygen species, 127 defects 128 and element compositions 129,130 on the surface of SMONs, but also the structural properties, i.e., porosity, 131 heterojunction properties [132][133][134] and conductivity 135,136 can affect the RT gas sensing performance.…”
Section: Yongqing Fumentioning
confidence: 99%
See 2 more Smart Citations
“…112 The aim of this topical review is to critically evaluate the design and structure of SMON-based gas sensors that may help guide the design of new devices. The performance of these SMON based gas sensors operated at RT could be improved significantly by modifying the SMONs using noble metal nanoparticles, [113][114][115][116] metal ions, [117][118][119] composites of multiple SMONs [120][121][122][123] and carbon nanomaterials. [124][125][126] In addition, not only the quantity of chemisorbed oxygen species, 127 defects 128 and element compositions 129,130 on the surface of SMONs, but also the structural properties, i.e., porosity, 131 heterojunction properties [132][133][134] and conductivity 135,136 can affect the RT gas sensing performance.…”
Section: Yongqing Fumentioning
confidence: 99%
“…Chemical and electronic sensitization of the SMONs can be realized by adding noble metals on their surface and thus can remarkably enhance their sensing properties. Surface modifications and introduction of defects on the surfaces and interfaces such as introduction of heterojunctions 134 and vacancies 117 influence the sensing performance of SMON sensing materials. Addition of carbon nanomaterials on the surface of SMONs can also significantly improve their conductivity and enhance their sensitivities at RT.…”
Section: Yongqing Fumentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, NiO nanosheets morphology got enormous interest for the various applications due to their extremely high surface area, ultrafine thickness, remarkable properties [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. For example, Wang et al synthesized network NiO nanosheets and utilized for the construction of high-performance lithium-sulfur battery [22].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…nanosheets were also used for gas and ion sensing [32][33][34]. Sun et al reported synthesis of NiO nanosheets decorated on TiO2 nanorods and used for improved photocatalytic activity [35].…”
Section: Accepted Manuscriptmentioning
confidence: 99%